Evaluation of Medical Student Satisfaction on the Implementation of Integrated Practicum in Indonesia Museum of Health and Medicine - Liem, Isabella Kurnia; Fitriyanti, Dini; Nasrul, Aldila Amini; Jonathan, Marcell Fablius (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The Indonesia Museum of Health and Medicine (iMuseum), since 2019, has been carrying out the Growth and Development Module Integration Practicum for medical students. This practicum integrates basic medical science (Embryology) and clinical (Children’s Health) within the scope of human development, from conception to adulthood. To assess the success of the program, an evaluation of student satisfaction questionnaire data has been carried out on the implementation of the 2020-2022 practicum in a cross-sectional manner. A total of 449 respondent data were successfully processed, consisting of FKUI internal (n=308) and external (n=141) student data. Overall, students have good satisfaction, (3.79; SD 0.36). External students have higher satisfaction (3.87; SD 0.23) compared to internal students (3.78; SD 0.32); independent-t test; t=3.395 (t>1.96); p=0.001 (p<0.05). However, this satisfaction score is not correlated with the value post-test (data for the External group 1; Spearman’s test p=0.412 [p>0.05]; rs=0.102). Mark post-test the average reached the number A, namely 86.08 (SD 7.77). It was concluded that the Growth and Development Module Integration Practicum has provided satisfaction to medical students properly.